2021
DOI: 10.1021/acs.jpca.1c06900
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Fate of the CH3SOO Radical from the CH3S + O2 Equilibrium

Abstract: The atmospheric oxidation mechanisms of reduced sulfur compounds are of great importance in the biogeochemical sulfur cycle. The CH 3 S radical represents an important intermediate in these oxidation processes. Under atmospheric conditions, CH 3 S will predominantly react with O 2 to form the peroxy radical CH 3 SOO. The formed CH 3 SOO has two competing unimolecular reaction pathways: isomerization to CH 3 SO 2 , which further decomposes into CH 3 and SO 2 , or a hydrogen shift followed by HO 2 loss, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 59 publications
5
35
0
Order By: Relevance
“…This is supported by the work of Chen et al. (2021), who also found that CH 3 S∙ oxidizes to SO 2 in near unit yield and not H 2 CS, a potential precursor to OCS.…”
Section: Chemical Mechanism For Ocs Production In the Oh‐oxidation Of...supporting
confidence: 62%
“…This is supported by the work of Chen et al. (2021), who also found that CH 3 S∙ oxidizes to SO 2 in near unit yield and not H 2 CS, a potential precursor to OCS.…”
Section: Chemical Mechanism For Ocs Production In the Oh‐oxidation Of...supporting
confidence: 62%
“…The atmospheric yield of SO 2 from the oxidation of MeSH by OH under low NO x was recently reported as 0.98 based on modeling results constrained by a laboratory oxidation study, which is in good agreement with the efficient production of SO 2 from MeSH proposed in our reaction scheme (Chen et al, 2021). We exploit this link between MeSH oxidation by OH and known DMS oxidation chemistry to develop a MeSH oxidation mechanism for implementation in a 0-D chemical box model as described further in the subsequent text.…”
Section: Atmospheric Fate Of Meshsupporting
confidence: 88%
“…The atmospheric yield of SO2 from the oxidation of MeSH by OH under low NOx was recently reported as 0.98 based on 135 modeling results constrained by a laboratory oxidation study, which is in good agreement with the efficient production of SO2 from MeSH proposed in our reaction scheme (Chen et al, 2021). We exploit this link between MeSH oxidation by OH and known DMS oxidation chemistry to develop a MeSH oxidation mechanism for implementation into a 0-D chemical box model as described further in the subsequent text.…”
Section: Oh + Ch Sh → Ch S + H O (R1)supporting
confidence: 88%
“…Model diel profiles of SO2 mixing ratios and PSO2 with and without MeSH emissions are shown in Fig 7 . In the campaign mean case MeSH emissions contribute 30% of the overall SO2 production (or a 43% increase in total SO2 production compared to the FDMS only case). The model yield of SO2 from MeSH oxidation was 0.99 which is comparable to an experimentally constrained model determination of the atmospheric yield of 0.98 (Chen et al, 2021). We include the full MeSH oxidation mechanism for 400 completeness due to its overlap with known DMS chemistry and ease of implementation in the box model.…”
Section: Impact Of Mesh On Marine Sulfur Dioxide Production 390mentioning
confidence: 52%
See 1 more Smart Citation